MSME Price Adjustment Strategy in Local Market Competition in Surabaya: A Review of Price Theory - Juliani Pudjowati; Susi Tri Wahyuni (Nomico, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Surabaya face complex challenges in establishing competitive pricing strategies amid dynamic local market competition. This study uses a systematic literature review approach to identify relevant price theories, analyze the price adjustment practices of MSMEs, and map challenges and opportunities in the context of the Surabaya market. Of the 943 publications identified, 27 selected articles were analyzed using thematic synthesis. The findings show that the majority of MSMEs (68%) still apply the cost-plus pricing model because of its convenience, but the trend towards value-based pricing (22%) and dynamic pricing (8%) is starting to be seen in MSMEs with higher digital literacy. External factors such as digitalization, consumer behavior, and innovation-based competition are key determinants of the success of a pricing strategy. Pricing training and the adoption of predictive technology have been proven to increase the efficiency and competitiveness of MSMEs. This research provides theoretical contributions through the synthesis of pricing models in the context of local MSMEs, as well as practical contributions in the form of strategic recommendations for business actors and policymakers.